Factors influencing intent-oriented behaviour of transport-energy saving measures among personnel of Dewan Bandaraya Kuala Lumpur - Chan, Shiau Cin (2014)
The major combustion of fossil fuels that releases large volumes of carbon dioxide into the atmosphere have contribute to climate change. To reduce the negative effects of climate change, one should first reduce his or her energy consumption. Energy conservation can be achieved through adoption of technological and behavioural changes. The main purpose of the study was to determine factors that affect intent-oriented behaviour of transport energy-saving measures. The factors investigated were perceived quality of train service, attitude towards energy conservation, perceived efficacy, knowledge of causes and impacts of climate change, and personal norm. A total of 700 self-administrated questionnaires were distributed across 24 main departments and 11 branches office in DBKL using quota sampling method. The final sample for the present study consisted of 403 DBKL personnel. Results indicated that the intent-oriented behaviour of transport energysaving measures among the DBKL personnel was at moderate level. Likewise, the respondents‟ possessed moderate to high levels on perceived quality of train service, attitude towards energy conservation, perceived efficacy, knowledge of causes and impacts of climate change and personal norm. Pearson correlation showed that there was no significant relationship between perceived quality of train service and the intent-oriented behaviour of transport energy-saving measures. Attitude towards energy conservation (r = 0.314, p ≤ 0.001), perceived efficacy (r = 0.432, p ≤ 0.001), knowledge of causes and impacts of climate change (r = 0.162, p ≤ 0.01), and personal norm (r = 0.255, p ≤ 0.001) were found to have significant positive relationships with the intent-oriented behaviour of transport energy-saving measures. The regression model explained 21% of the variance in the intent-oriented behaviour of transport energy-saving measures. Perceived efficacy, attitude towards energy conservation and personal norm are the predictors that were found to significantly affect the intent-oriented behaviour of transport energy-saving measures. On the whole, intent-oriented behaviour was shown to be strongly related to psychological variables, whereas contextual or external variable was not influential. Several implications were drawn from the present study, and these could be utilized by policy makers to plan appropriate programmes and implement policies for transportrelated energy conservation.